2012
DOI: 10.1111/j.1529-8817.2012.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

ABSENCE OF EVIDENCE IS NOT EVIDENCE OF ABSENCE: IS STEPHANODISCUS BINDERANUS (BACILLARIOPHYCEAE) AN EXOTIC SPECIES IN THE GREAT LAKES REGION?1

Abstract: The eutrophic, freshwater diatom species Stephanodiscus binderanus (Kütz.) Willi Krieg. has long been considered a nuisance exotic alga introduced from Eurasia to the Great Lakes in North America in the early to mid-20th century. However, our paleolimnological data from Lake Simcoe, Ontario, provide unequivocal evidence that this taxon has been present in the Great Lakes region since at least the late 17th century. Subfossil diatom valves were identified and enumerated at high resolution in (210) Pb-dated sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Nevertheless, the possibility that G. semen 's presence was previously undetected due to very low abundance in cell numbers remains. For example, a recent study showed that the freshwater diatom Stephanodiscus binderanus , which was described as an exotic species in the Great lakes since the mid-20 th century, was already present in these lakes since a least three centuries [46]. That study shows that a species might be native although other evidence suggested that it was introduced recently.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the possibility that G. semen 's presence was previously undetected due to very low abundance in cell numbers remains. For example, a recent study showed that the freshwater diatom Stephanodiscus binderanus , which was described as an exotic species in the Great lakes since the mid-20 th century, was already present in these lakes since a least three centuries [46]. That study shows that a species might be native although other evidence suggested that it was introduced recently.…”
Section: Discussionmentioning
confidence: 99%
“…However, documenting that taxa did not live in an area prior to present day is difficult, as is the case for lost taxa when we can only observe a very small fraction of the organisms living in a habitat. Absence of evidence is not evidence of absence (e.g., Hawryshyn et al, 2012). Many diatoms develop deformities in response to heavy metal pollution, which are clear signs of pollution altering organism condition.…”
Section: F Measuring Biological Condition and Ecosystem Servicesmentioning
confidence: 97%
“…Although paleolimnological studies have only rarely been used to determine species introductions (e.g., Smol 1988;Hawryshyn et al 2012), these approaches often offer the only sources for generating such data. The occurrence of didymo valves throughout the ϳ40-year-old sediment record at LAS, in combination with direct observations from early 20th century diatom surveys (Bailey 1910(Bailey , 1912Miller 1915), refute claims that this diatom is an introduced species to rivers in eastern Canada.…”
Section: The Historical Occurrence Of Didymo In Gaspésiementioning
confidence: 99%
“…Furthermore, conventional sampling efforts of microorganisms in most ecosystems are often insufficient to demonstrate which taxa are truly absent at a given point in time. Therefore, it becomes difficult to determine if diatom species can truly be considered "introduced", including didymo (e.g., Kirkwood et al 2007;Spaulding et al 2010;Hawryshyn et al 2012). Additionally, diatomists from the early 20th century observed this taxon (syn.…”
Section: Introductionmentioning
confidence: 98%